RECYCLING OF LITHIUM ION BATTERY: KINETIC STUDY OF REDUCTION OF LITHIUM COBALT OXIDE CATHODE USING GRAPHITE REDUCTOR AND SODIUM CHLORIDE ADDITIVE - Giri Natha, Made
The production of lithium-ion batteries (LIB) is predicted to increase every year and consequently, the number of lithium-ion battery waste will increase in the future. Lithium-ion battery waste will impose environmental problems if not handled properly. On the other hand, lithium-ion batteries contain elements with high concentrations and economic value, such as cobalt and lithium. Indonesia does not have a significant amount of lithium and cobalt resources and thus the lithium-ion battery waste is potential to be used as a secondary source of lithium and cobalt elements. One of the options to recover these elements from lithium-ion battery waste is through a high-temperature recycling process. In this study, the kinetics of the reduction LiCoO2 cathode study has been conducted using graphite and NaCl as an additive. The experiment started by characterizing the LiCoO2 sample used as the raw material in this study. Samples were analyzed using X-ray Diffraction (XRD) to determine their crystal structures and purity of LiCoO2. In addition, changes in weight and heat transfer when LiCoO2 samples were reacted with graphite and NaCl salt were analyzed using a Thermogravimetric - Differential Thermal Analysis (TG-DTA) tool. Subsequently, 1.5 grams of LiCoO2 samples were mixed and briquetted with 0.3 grams of starch. The briquettes were then calcined and sintered in a muffle furnace at a maximum temperature of 900oC for 290 minutes. The sintered samples were weighed to determine its initial weight before its being reduced. Each sample was then arranged in a porcelain crucible with graphite plates used as its base and lid. Graphite powder was also added surrounding the sample as a protective layer from the oxidation with the surrounding atmosphere. In the experiment with the addition of NaCl, NaCl salt was added to the graphite powder protective layer according to the targeted variation. The sample is then reduced in the muffle furnace at the selected temperature variations, including 900 ?C, 1000 ?C, 1100 ?C, 1200 ?C, and 1300 ?C. Reduction time was varied from 5 minutes, 15 minutes, 30 minutes, 60 minutes, to 120 minutes. After the reduction process, the sample was removed from the furnace and cooled naturally until it reached room temperature. The weight of the reduced briquettes was weighed using an analytical balance and then further characterized using XRD and Scanning Electron Microscope-Energy Dispersive Spectroscopy (SEM-EDS). XRD analysis was conducted to identify the compounds formed in the experimental samples, while SEM-EDS analysis was conducted to identify the microstructure and composition of the experimental samples. The experimental data were analyzed to estimate the LiCoO2 reduction mechanism, to study the effect of reduction temperature, the reduction time, and NaCl addition to the reduction degree of LiCoO2 reduction, and also to determine the rate-controlling step of LiCoO2 reduction. The TG-DTA results show that the reduction of LiCoO2 occurs through the formation of CoO and Li2CO3 compounds at temperatures below 650 ?C, which is then followed by metal formation at temperatures above 650 ?C, and the formation of Li2O or LiCl compounds at temperatures above 840 ?C. Temperature affects the type of compound formed during the reduction process. At temperatures below 900 ?C lithium is stable as Li2CO3 compounds, at temperatures above 900 ?C lithium is stable as Li2O, and at a temperatures above 1300 ?C lithium evaporates as LiCl gas. The experimental results show that increasing the temperature increases the weight loss of the sample which indicates an increase in the degree of reduction of LiCoO2. The highest degree of metal reduction was found at 1300 ?C where all the cobalt in the cathode material had been converted to metal. The addition of NaCl to the cathode reduction process resulted in the formation of LiCl salt and Li2O. The molten salt evaporated at temperature above 1100oC. Analysis of the kinetic data showed that the reduction process of LiCoO2 was controlled by a second-order chemical reaction with the percentage of sample weight reduction which can be formulated as follows: = 39,83% ? [1 ? 1 ?[1 + [44667exp(19934?T)]t]].